Hemoglobin regulates the migration of glioma cells along poly(ε‐caprolactone)‐aligned nanofibers. (24th July 2014) - Roth, Alexander D.; Elmer, Jacob; Harris, David R.; Huntley, Joseph; Palmer, Andre F.; Nelson, Tyler; Johnson, Jed K.; Xue, Ruipeng; Lannutti, John J.; Viapiano, Mariano S.
<x xml:space="preserve">Abstract</x> Aligned fibers have been shown to facilitate cell migration in the direction of fiber alignment while oxygen (O2)‐carrying solutions improve the metabolism of cells in hypoxic culture. Therefore, U251 aggregate migration on poly(ε‐caprolactone) (PCL)‐aligned fibers was studied in cell culture media supplemented with the O2 storage and transport protein hemoglobin (Hb) obtained from bovine, earthworm and human sources at concentrations ranging from 0 to 5 g/L within a cell culture incubator exposed to O2 tensions ranging from 1 to 19% O2. Individual cell migration was quantified using a wound healing assay. In addition, U251 cell aggregates were developed and aggregate dispersion/cell migration quantified on PCL‐aligned fibers. The results of this work show that the presence of bovine or earthworm Hb improved individual cell viability at 1% O2, while human Hb adversely affected cell viability at increasing Hb concentrations and decreasing O2 levels. The control data suggests that decreasing the O2 tension in the incubator from 5 to 1% O2 decreased aggregate dispersion on the PCL‐aligned fibers. However, the addition of bovine Hb at 5% O2 significantly improved aggregate dispersion. At 19% O2, Hb did not impact aggregate dispersion. Also at 1% O2, aggregate dispersion appeared to increase in the presence of earthworm Hb, but only at the latter time points. Taken together, these results show that Hb‐based O2 carriers can be utilized to improve O2 availability and the migration of glioma spheroids on nanofibers. © 2014 American Institute of Chemical Engineers Biotechnol. Prog., 30:1214–1220, 2014